Sealing Ability of Endodontic Cements: An In Vitro Study - Amira Kikly; Sabra Jaâfoura; Dorra Kammoun; Saida Sahtout (Hindawi Limited, 2020)
The root canal system must be obturated using a hermetic seal to prevent the penetration of microorganisms and bacterial toxins into the endodontic system. The principles of adhesive dentistry have been increasingly used in endodontics. In fact, resin-based sealers are increasingly used. The objective of this study was to evaluate, in vitro, the sealing ability of resin cement in comparison with calcium hydroxide-based cement. Materials and Methods. Eighty root canals were prepared with the Tilos system and were randomly divided into four groups according to the filling material. The best combination was evaluated on the basis of its sealing ability. The dye infiltration degree was evaluated using both a stereomicroscope after diaphanization and the dye rise test. Results. A significant difference was observed between the four obturation systems with regard to the number of infiltrated walls (p=0.014) and the infiltration depth (p=0.025). The group of teeth obturated with EndoREZ® and EndoREZ® gutta cones differ significantly from the group obturated with EndoREZ® cement and gutta-percha cones in terms of apical sealing (p=0.011). A significant difference was also observed between the group of teeth obturated using EndoREZ® gutta cones and EndoREZ® cement and the group of teeth obturated with EndoREZ® cement (p=0.026). Conclusion. When used with EndoREZ® gutta cones, EndoREZ® cement showed the best sealing ability, particularly in the apical region. When used with gutta-percha cones, Acroseal and EndoREZ® cements exhibited similar sealing abilities.